Coupled Dynamics of Ecological Footprints under Energy Transition, Land Use Change, and Urbanization: An Econometric Systems Analysis - Nihar Chinchwade; Shipon Chandra Barman; Md Arman Hossain; Mitu Karmakar (Research Parks Publishers, 2024)
Background: Ecological footprint changes is determined through measuring the interrelations amongst urban development, land-use transformation, energy transition and GDP growth. An econometric system analysis builds a foundation for modeling these coupling systems and provides insight into the future of these connections. The analysis also highlights ongoing energy transitions influence ecological footprint dynamics alongside urbanization and land use change. Methods: This study used an integrated econometric systems approach to analyze the dynamics of energy footprints (EFs) between 1990-2023. Descriptive statistics provide information about the long-term trends (up), Pearson’s correlations allow for analysis of relationships between variables, while PCA reveals the major determinants of Energy Footprints with relative contributions through weighted coefficients. The Vector Error Correction Model provides insight into both short-term adjustments and long-term equilibrium for Energy Footprints, urbanization, land-use change, land surface temperature, Normalized Difference Vegetation Index, energy transition, and GDP per capita. Results: Findings show that the continued growth of cities and changing land uses are putting significant ecological pressure. The VECM indicates that 41% of annual deviations from the long-term mean (average) are being corrected by the system, demonstrating the long-term relationship between these two systems is stable. Conclusion: To rebalance the demand for growth against the ecological capacities of our planet, integrated land use planning, green infrastructure, and sustainable development policies must be created as a result of combined impacts of urbanization, land-use changes and changes in energy consumption.